The Real World of Democratic Theory - Shapiro, Ian (Book collections on Project MUSE., 2011)
In this book Ian Shapiro develops and extends arguments that have established him as one of today's leading democratic theorists. Shapiro is hardheaded about the realities of politics and power, and the difficulties of fighting injustice and oppression. Yet he makes a compelling case that democracy's legitimacy depends on pressing it into the service of resisting domination, and that democratic theorists must rise to the occasion of fashioning the necessary tools. That vital agenda motivates the arguments of this book.